Lucha olímpica como deporte de contacto y su influencia en los adolescentes de la Liga Deportiva cantonal de Quevedo Provincia de Los Ríos - Gavilanes Ponguillo, Cristhian Paul (2018)
The practice of the Olympic fight is very long and of great effort, there are many hours that your athletes must dedicate to their training, as well as, there are many factors that must be taken into account when entering the children and adolescents, who during their first days face very hard situations of great dedication and perseverance. On the other hand there are many requirements in terms of materials, equipment, resources and other details that have to be present in all training, which together make it possible to meet the strict requirements that require the practice of the Olympic fight. Otherwise it is necessary to manage and develop various strategic alternatives to achieve massification, motivation and awaken the interest of children and adolescents, who once they know and practice it are involved so that their efforts are remitted to its results, the same ones that must be recognized by the sports federations developing competences for their active participation. For the development of this work, a non-experimental design was applied, with an exploratory, descriptive-descriptive approach, with a population that worked as shown by its size of 39 athletes and four coaches, to whom surveys and interviews were applied. the same ones that after analyzing and discussing the results it was concluded that it is necessary, among other things, to disseminate and promote wrestling in the lower categories by means of a manual indicating the aspects to be found in the practice of the boys and girls and also to Through systematic competitions to capture the attention of adolescents and achieve their overcrowding.